Peri-Implant Behavior of Tissue Level Dental Implants with a Convergent Neck - Agustín Panadero, Rubén; Bermúdez Mulet, Irene; Fernández Estevan, Lucía; Solá Ruíz, María Fernanda; Marco Pitarch, Rocío; García Selva, Marina; Zubizarreta Macho, Álvaro; León Martínez, Raquel (My University, 2021)
Introduction: The aim of this retrospective study was to analyze the radiographic periimplant bone loss of bone level implants and tissue level implants with a convergent neck in screw-retained single crowns and in screw-retained fixed partial prostheses, after two years of functional loading. Materials and methods: The sample was divided into two groups according to their type: Group I: supracrestal implants with convergent transmucosal neck; Group II: crestal implants. In each group we distinguish two subgroups according to the type of prosthetic restoration: single crowns and a three-piece fixed partial prosthesis on two implants. To quantify bone loss, parallelized periapical radiographs were analyzed at the time of implant placement and after two years of functional load. Results: A total of 120 implants were placed in 53 patients. After statistical analysis it was observed that for each type of implant bone loss was 0.97 ± 0.91 mm for bone level and 0.31 ± 0.48 mm for tissue level. No significant differences were found regarding the type of prosthesis and the location (maxilla or mandible) of the implants. Conclusions: Tissue level implants with a convergent transepithelial neck exhibit less peri-implant bone loss than bone level implants regardless of the type of prosthesis. Keywords: bone loss; bone level; tissue level; single crown; fixed partial prosthesis